Contribution of Underutilized Plants in Food and Livelihood Security in Tinsukia District - Gohain, Sanchayeeta; Borthakur, Sanjoy; Amonge, Priyanka; Neog, M. (International Journal of Economic Plants, 2022)
Underutilized plants though have a great potential towards contribution of improvement of livelihood income and nutritional security, they are not properly explored. A study was carried out in Tinsukia District with the help of a questioner and focus group discussion with the objective to identify the importance of underutilized crops at farmer’s level. Data was collected from 120 families and the study showed that there are many minor underutilized crops mainly fruits (40%), leafy vegetables (54.5%), and herbals (29%) which are not only subsidizing to the food requirement and nourishment of the family but also generating an extra income at household level and also are being used to treat the minor disorders at local level.